2011
DOI: 10.1258/jtt.2010.100618
|View full text |Cite
|
Sign up to set email alerts
|

Telesurveillance of circular frame pin sites: one year's experience at a specialist unit

Abstract: Circular frame treatment for limb reconstruction involves repeated follow-up visits, and a substantial number of these appointments are for pin site review only. We have encouraged our frame patients to take photographs of their pin sites when they carry out their weekly dressing changes. The photographs are taken with mobile phones or digital cameras by the patients themselves, and the images sent to us by email. We reply within 24 hours, with either reassurance or appropriate instructions as indicated. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Chanussot-Deprez showed that photography in rural areas can be used to allow adequate wound management with advice from distant centres while saving on travel costs for patients and the health system [9] . Khan et al used digital photography to follow pin sites from external fixators in 5 patients over a year [10] . In this study patients self-photographed their wound sites and emailed them to the treating physicians and all found this a highly satisfactory way of reducing outpatient visits.…”
Section: Discussionmentioning
confidence: 99%
“…Chanussot-Deprez showed that photography in rural areas can be used to allow adequate wound management with advice from distant centres while saving on travel costs for patients and the health system [9] . Khan et al used digital photography to follow pin sites from external fixators in 5 patients over a year [10] . In this study patients self-photographed their wound sites and emailed them to the treating physicians and all found this a highly satisfactory way of reducing outpatient visits.…”
Section: Discussionmentioning
confidence: 99%